Introducing in situ activated sludge microscopy: a case study on reducing precipitant use - Bähr, Simon; Weigand, Philipp; Gasparini, Soria; Treiber, Christoph; Schulz, Felicitas; Wasenmüller, Oliver; Suhr, Hajo; Wiedemann, Philipp (Journal of Water Process Engineering, 2025)
Biological wastewater treatment using the activated sludge process (ASP) is a key method for removing eutrophying substances from wastewater and protecting the environment. The structural composition of the activated sludge, influenced by filamentous bacteria, plays a decisive role in the sedimentation capacity of the sludge. Excessive growth of filamentous bacteria can lead to operational problems such as bulking or floating sludge, which impairs the purification performance of the process. In practice, expensive, naturally limited precipitants are often used to remove these bacteria. In this study, a novel high-resolution in situ immersion microscope (ISM) was developed and used directly in the activated sludge basin of a municipal wastewater treatment plant over a period of more than 18 months in 2023, 2024 and 2025. Hourly, 200 microscopic images of the activated sludge were taken. An AI-based algorithm for measuring the length of filamentous bacteria was developed to analyze the images. The new measurement parameter, the in situ microscopic total extended filament length (ismTEFL), enables continuous and automated monitoring of bacterial growth. The results show a high correlation between the ismTEFL value and the sludge volume index (SVI), which confirms the suitability of the system as an early warning indicator for operational problems. As a case study, the plant operators were able to quickly react to the increase of filamentous bacteria which improved the settling behaviour of the sludge and saved more than 6000 l of polyammonium chloride (PAC). The presented method offers an innovative solution for process monitoring in wastewater treatment plants.